Skin, gut, and lung barrier: physiological interface and target of intervention for preventing and treating allergic diseases - Berni Canani, Roberto; Caminati, Marco; Carucci, Laura; Eguiluz-Gracia, Ibón (Wiley, 2024)
The epithelial barriers of the skin, gut, and respiratory tract are critical interfaces between the environment and the host, and they orchestrate both homeostatic and pathogenic immune responses. The mechanisms underlying epithelial barrier dys-function in allergic and inflammatory conditions, such as atopic dermatitis, food al-lergy, eosinophilic oesophagitis, allergic rhinitis, chronic rhinosinusitis, and asthma, are complex and influenced by the exposome, microbiome, individual genetics, and epigenetics. Here, we review the role of the epithelial barriers of the skin, digestive tract, and airways in maintaining homeostasis, how they influence the occurrence and progression of allergic and inflammatory conditions, how current treatments target the epithelium to improve symptoms of these disorders, and what the unmet needs are in the identification and treatment of epithelial disorders.
Keywords: Alergia; Biologics; IL-25; IL-33; Tight junctions; TSLP